Swimming training on moderate intensity significantly reduces total cholesterol and bodyweight on hypercholesterolemic rat model - Sholikhah, Anindya Mar'atus; Ridwan, Mochamad (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
It is well established that regular exercise has many positive benefits on health. Exercise at the appropriate intensity and level has been shown to improve lipid profile and reduce the risk of cardiovascular disease. This study investigates the effect of swimming training on total cholesterol levels and body weight in male Wistar rats. Thirty rats weighing 150-200 grams were randomly divided into one control (C) and two treatment groups (ST=swimming training, SED=sedentary activity). Rats in control (C) group were fed a standard diet, while rats in both treatment groups were fed high-fat diet-induced hypercholesterolemia for three weeks. Rats in ST were then swim-trained at moderate intensity for 30 minutes/day, six days a week for three weeks, and rats in SED were left without exercise stimuli. Body weight was measured weekly. At the end of the experimental period, intracardiac blood samples were drawn to measure the total cholesterol level. Findings revealed that rats’ bodyweight (p=0,045) and blood cholesterol (p=0,034) in ST group were significantly lower compared to SED. It indicates that swimming exercise is shown to be effective in weight loss and reducing blood cholesterol level in hypercholesterolemic rats.